Sosialisasi Pemahaman dan Penerapan Prototipe Solar Cell di Sekolah Menengah Kejuruan Voctech 1 Tangerang - Vivi Monita; Cut Faradina; Fathiyah Syafana (LPkM Universitas Bakrie, 2026)
Solar energy is an abundant and environmentally friendly renewable energy source; therefore, its utilization through solar cell technology is highly relevant in addressing energy challenges in the Industrial Era 4.0. However, many Vocational High School (SMK) students still lack a deep understanding of the working principles and applications of this technology. The activity of socializing and implementing solar cell prototypes at SMK Voctech 1 Tangerang aims to enhance students' understanding of the concept, benefits, and operation of solar cells, as well as provide direct practical experience in installing and operating simple solar power systems. This activity involves delivering theoretical material on solar energy, types of solar cells, and implementing a 360 WP solar cell prototype that can be used to charge electronic devices, serving as a simulation of alternative energy sources. The results of the activity showed that students were able to conceptually and technically understand solar cell technology and were able to install and operate the prototype well. Thus, this activity is expected to be the first step in fostering students' awareness and skills in utilizing renewable energy independently and sustainably.